Electrocardiographic characterization of cardiac functionality in healthy NMRI mice strain (Gaceta de Ciencias Veterinarias, 2020)
In the present study, we have characterized under anesthesia with sodium pentobarbital and ketamine, electrocardiographic parameters in 74 healthy male adult mice of the NMRI strain, in bipolar configuration, using needle-type electrodes positioned in the subcutaneous tissue, using DI, DII, DIII and AVF derivations. We obtained that, typical electrocardiographic morphology of a healthy NMRI mouse contains: a predominantly positive monophasic P wave, a QRS complex with a small Q wave, a positive R wave and a negative S wave; which continues with an upward wave with a positive deflection, followed by a descending wave, whose decay can be defined with two components: fast (t =  4 ms ) and slow (t =  67 ); the slow component can delineate a superior hemiconvexity or a concavity below the isoelectric line before reaching it. The upward wave after the S wave and the fast decay component would define the J wave; while the slow component together with the upper hemiconvexity or with the lower concavity the T wave. Conclusion: the presented results define the numerical and morphological electrocardiographic ranges of healthy NMRI mice that it would have a reference value to compare with other strains and diseased mice.Keywords: ECG, electrocardiography, NMRI mice, J wave